“The Last One Turns the Light off”. Polish Prose after the Year 2000 in the Context of EU Migration - Nęcka, Agnieszka (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
This article focuses on the emigration/migration issue depicted in Polish literature written after the year 2000. The examples discussed prove that we are dealing with two variants in the depiction of emigrants’ experience. On the one hand, we can talk about a positive pattern where emigration is treated as an adventure, perceived as breaking free from the existing obligations and imposed rigours. On the other hand, one may find several negative patterns, in which emigration is a necessary evil. The author notices a clear gender difference in the presentation of the emigrant experience: male narratives tend to be more depressing, presenting the protagonists as degenerated and humiliated, while female authors drift towards “chick lit,” depicting their protagonists as developing professionally and emotionally.
Translated by Elżbieta Rokosz.
Keywords: emigration; migration; Polish prose; gender